A tribute to Dr. David Barmes - Editorial (Blackwell Synergy, 2001)
The world of dental public health lost one of its finest leaders when David Barmes passed away on January 13, 2001. He was at his family home in Sydney, and he died peacefully in his sleep at age 69.